The importance of integrating flash cards as a visual tool inprove the retention of the meaning of verbs in the students of the ninth year of basic education - Patiño Morocho, María de Lourdes; Tepán Zhagüi, Tania Silvana
We have focused this project on the use of flashcards with activities that the English teachers can use in the teaching-learning process. These activities are created not only to present new vocabulary, and practice pronunciation, but also to call the attention of the students to participate in class using the verbs. The use of flashcards helps teachers to introduce a new word through an image and that image is about any vocabulary word and in this case is about verbs. Moreover, Andrew Cohen mentions some advantages of the flashcards. The main is that flashcardsengage a mental faculty known as active recall which is a principle of efficient learning, which claims the need to actively stimulate memory. Also there are three types of learners, kinesthetic learners who learn by doing, auditory learners learn by listening and visual learners learn by looking. All of them are important and the activities presented in this project will help to introduce the verbs in ninth year of basic education to visual learners achieving a long-term retention.